Analisis Emisi GRK dan Konversi Energi pada Produksi Minyak Jarak (Ricinus communis L.) dengan Metode Life Cycle Assessment (LCA) - Ramdhani, Medy; Yani, Mohammad; Ismayana, Andes (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Castor oil (Ricinus communis L.) is a renewable, multifunction vegetable oil, used in wide range of chemical industry feedstock. Nowadays, a product derived from castor has able to replace petroleum-based chemical feedstock. In spite of its renewable characteristic, castor oil production has to meet the environmental sustainability. This study was conducted to determine numbers of input and output used, as well as, their impact to the environment in the production processes. Life Cycle Assessment (LCA) method was used to determine the input, output and environmental impacts of castor oil production. The result is, that the needs for a ton of castor oil are: 0.97 ha of land, 1.06 kg of seeds for plantation, 0.27 tons of fertilizer, 7.7 liters of petrol, 219.71 liters of diesel, 2.43 tons of seeds for processing purpose, and 1 187.54 liters of water. The production process itself emits 1.03 tons CO2-eq of greenhouse gas (GHG). Reduction to environmental pressure could be accomplished by replacing fossil fuel with castor cake during production to reduce 153.19 liters of diesel usage equals with 0.43 tons CO2-eq emission for a ton castor oil.